Gardnerella fibrinogen-binding protein as a candidate adherence factor - Aistė Bulavaitė; Justas Dapkūnas; Raminta Reškevičiūtė; Indrė Dalgėdienė; Lukas Valančauskas; Lina Baranauskienė; Milda Plečkaitytė (Frontiers in Cellular and Infection Microbiology)
Bacterial vaginosis (BV), a form of vaginal dysbiosis, is associated with numerous adverse reproductive and obstetric outcomes. Gardnerella spp. are among the key bacteria identified in most BV cases. The formation of a polymicrobial Gardnerella-dominated biofilm on the vaginal epithelium is a characteristic diagnostic marker of BV. Gardnerella colonization and biofilm formation indicate a significant adhesion potential, the determinants of which remain unexplored. In this initial approach to identify Gardnerella adhesins, we analyzed the Cna protein located on the G. vaginalis ATCC 14018 cell surface as determined previously. Structure modeling of Cna (designated Grd Cna) revealed that the protein contains N2 and N3 domains with an immunoglobulin (IgG)-like fold, which shows structural homology to the corresponding domains in SdrD and UafA proteins of the microbial surface component recognizing adhesive matrix molecules (MSCRAMMs) family. A single B domain shares structural similarity with the corresponding domain of Sdr proteins. The R region is rich in PKD repeats, while the C-terminal contains a non-canonical LVNTG cell wall sorting motif. The cna gene was predominantly detected in G. vaginalis isolates but was absent in other commonly identified Gardnerella species isolates. The recombinant Grd Cna protein binds dose-dependently to human fibrinogen but does not interact with fibronectin or collagen types I, III, or IV. Cna-positive G. vaginalis cells adhered to immobilized fibrinogen; however, recombinant Cna did not inhibit this binding, suggesting that Cna may not be a major adhesin mediating G. vaginalis adherence to this ECM component.